Propagation and culture system of local leechess - Ahmad Anwar Mohamed Ismail; Ibrahim Che Omar; Zulhisyam Abdul Kari @ Abdullah; A.S Mamat (Universiti Malaysia Terengganu, 2011)
This particular research work was one of the few that have been reported on the basis requirements for culturing of local leeches including reproduction and also the behaviour of the animal. In this study effect of different cultures for leech-rearing in laboratory conditions on the reproductive performance of local leech was examined. After 91 days (3 month) of culturing, the number of cocoons produced was significantly different between the two conditions (p<0.05). For the leeches cultured in the tank with 1 cm depth of non-chlorinated water with soil height of about 5cm, cocoon deposition number was optimal, depositing an average of 3.67+0.58 compared with culture 2 where there was no cocoons produced by broodstock. Mortlities of broodstock leeches differed significantly under the two culturing methods (p<0.05). Culture i gave the lowest mortality rate with mean and standard deviation of 2.67+2.3% compared with the second culture which gave the highest mortality rate of 40+10.58%. The study also discussed the reproduction and the behaviour of the local leeches.